Analisis Dispersi Polutan SO2 dan NOx dengan Model AERMOD (Studi Kasus: PLTU Pangkalan Susu PT. PLN Indonesia Power PGU) - Syukri Hadi Novri Siregar; Isra’ Suryati; Lies Setyowati; Rahmi Utami; Meidina Zulfa Hanie; Affandi Lubis; Randy Zulkarnain (Jurnal Serambi Engineering, 2025)
Coal-fired power plants produce emissions of particulate matter and gases such as NOx, SO2 and Hg, which can have adverse effects on living organisms. Modelling is one method used to estimate the impact of an emission. In addition, the pollutant dispersion model can be used to assess the compliance of an industry's ambient air sampling points. The model used in this study is AERMOD, which is a steady state model influenced by the existing meteorological conditions. The study site is Pangkalan Susu PLTU (2x200 MW) with NOx and SO2 parameters. The purpose of this study was to analyse the distribution patterns of NOx and SO2 concentrations using the AERMOD model, to analyse the differences in pollutant distribution models in wet and dry months, and to validate the modelling with field observations. The results showed that the maximum concentration of the model was 17.4 µg/m3 for NOx and 16.2 µg/m3 for SO2. The simulation results of the AERMOD model show the impact distribution area to the southeast in the wet month and to the northeast in the dry month of the Pangkalan Susu PLTU. The validation results show that the model is in agreement with the field observations.